Ekstraksi Minyak Ulat Hongkong Menggunakan Metode Soxhletasi dengan Pelarut Petroleum Eter - Rietias Sarinastiti Nurmin; Adrian Satria Kemal; Maya Ramadianti Musadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Due to global food issues, alternative sources are needed to replace oil such as vegetable and animal oils to produce oil-based products. However, increasing issues about animal-derived products are becoming an environmental problem. Yellow mealworm as a potential source of oil, has attracted the interest of researchers due to its ability to accumulate fat by feeding on organic waste. This study investigates the effect of variation in petroleum ether solvent ratio and extraction time on the yield, acid number and water content of Yellow mealworm. The variations of the ratio of caterpillar and solvent used were 1:6, 1:8, and 1:10, with extraction time of 5, 6, and 8 hours at 65°C. The best results of this study showed that the ratio of caterpillar and solvent 1:10 with extraction time of 8 hours produced the highest oil yield of 15% with FFA content of 6.88%. Extraction using the soxhletation method with petroleum ether solvent can reduce the water content from 80% to 0.21%.